Communicative abilities development among students-future teachers, while learning the subject "Russian language and culture of speech" - Hvashaevskaya D. I. (Pedagogical excellence and pedagogical technologies, 2016)
this article is devoted to the description of classes on discipline "Russian language and culture of speech" that are based on a variety of pedagogical techniques, promoting the development of communicative abilities of students who are future teachers: gaming, information-related and project technologies and also case-based technologies.
Keywords: проектная технология; игровая технология; педагогические технологии; коммуникативные способности; кейс-технология; Information technology; communication skills; case-technology; gaming technology; информационная технология; engineering technology; pedagogic technology